PRINSIP ROBUST DALAM ENVIRONMENTAL GOVERNANCE PADA PERATURAN DAERAH KABUPATEN SUKOHARJO NOMOR 5 TAHUN 2023 - Muta'al, Muhammad Rofiud; Widayanti, Putri Wahyu (Jurnal Inovasi Daerah, 2023)
Industrial growth is one of the consequences of national development. Industrialization certainly has both positive and negative impacts. Environmental concerns, especially environmental damage that occurs due to industrialization, are currently still massive in Sukoharjo Regency. The case of environmental pollution in Sukoharjo has caused serious attention from policy makers to create environmentally based policies such as the application of the concept of environmental governance. This research will discuss the application of robust principles in environmental governance which consists of four aspects, namely Legitimate, Connected, Nested and Polycentric in Sukoharjo Regency Regional Regulation Number 5 of 2023 concerning environmental protection and management. The research method is normative legal research with a descriptive presentation and using a statutory approach. The results of this research show that the Sukoharjo Regency Regional Regulation Number 5 of 2023 concerning environmental protection and management has met the three aspects of the Robust Principle, namely the Legitimate, Connected and Polycentric aspects and has not fulfilled the Nested element.